Risk Assessment for Sustainable Hiking: A Conservation-Based Approach on the Cibodas–Gede Trail using Hazard Identification, Risk Assessment, and Determining Control (HIRADC) - Bahtiar Miftah; Ratna Sari Hasibuan; Abdul Rahman Rusli (Green Insight Solutions, 2025)
Special interest hiking tourism involves risks that can be minimized through thorough preparation and effective management. This study aims to identify potential hazards, assess risks, and propose control measures to enhance climbing safety within Mount Gede Pangrango National Park (TNGGP). The Hazard Identification, Risk Assessment, and Determining Control (HIRADC) method was employed, involving interviews with experienced trail managers, including two porters, two guides, and TNGGP officials with over one year of trail management experience. The results indicate seven vulnerable points along the Cibodas–Gede Peak Trail, where potential hazards have been identified. Based on assessments of probability and severity, five locations were categorized as high-risk zones: The Gayonggong Swamp Bridge, Hot Water Trail, Sela Crater Trail, Rante Climbing Trail, and the Bayangan–Gede Peak segment. These risks can be mitigated through a hierarchy of controls, including elimination, substitution, administrative controls, engineering controls, and the use of personal protective equipment. With a planned and conservation-based risk management approach, hiking activities in TNGGP can be conducted safely and sustainably, without compromising ecosystem functions or disturbing protected wildlife habitats. Such an approach is crucial for maintaining the delicate balance between conservation objectives and the sustainable use of ecosystem services for nature-based tourism.